Enhancing Elementary Students' Mathematical Reasoning through Realistic Mathematics Education: A Quasi-Experimental Study on 3D Geometry - Uliya Khoirun Nisa; Eko Kuswanti; Khoirotun Nadiyyah; Muhamad Nurulhayah (MASI Mandiri Edukasi, 2026)
This study addresses the limited empirical evidence on the effectiveness of the Realistic Mathematics Education approach in improving elementary students' mathematical reasoning skills, particularly in three-dimensional geometry. The objective of this research is to examine whether the Realistic Mathematics Education approach significantly enhances fifth-grade students' mathematical reasoning abilities in learning three-dimensional geometry. The study employed an applied quasi-experimental design with a Non-Equivalent Control Group. Two fifth-grade classes at SD Muhammadiyah Ngijon 1 were selected as the experimental and control groups. Data were collected through pretest and posttest using a validated and reliable five-item essay test that measured students' mathematical reasoning skills. Data analysis was conducted using the Shapiro-Wilk normality test, Levene homogeneity test, Independent Samples t test, and normalized gain analysis. The findings revealed a statistically significant difference between the posttest scores of the two groups (p = 0.031), which is lower than the 0.05 threshold. The experimental group achieved an N-Gain score of 79.75 percent, categorized as effective, while the control group achieved 75.20 percent, categorized as quite effective. These results demonstrate that the Realistic Mathematics Education approach is more effective, both statistically and pedagogically, in improving students' mathematical reasoning skills in three-dimensional geometry through meaningful, real-life contextual learning.